Enhancing animal welfare and improving production performance of feedlot cattle by introducing forms of environmental enrichment - Kahl, Cornelia Erika Iris (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.